Teaching Reading through Cooperative Learning at Islamic Junior High School Jember in the Academic Year 2006/2007 - Moch. Imam Machfudi (Fenomena, 2008)
The low achievement of Indonesian secondary students in reading comprehension remains a pressing issue in English language teaching. A major theoretical concern is whether cooperative learning can effectively address this problem by shifting from teacher-centered to student-centered instruction. This study aims to describe the process of teaching reading using a cooperative learning approach and to improve students’ reading comprehension. To achieve this goal, the researcher employed a Classroom Action Research (CAR) design based on Kemmis and McTaggart’s model, implementing one cycle of planning, action, observation, and reflection at SMP Islam Jember in the 2006/2007 academic year. Data were collected through observation sheets, quiz results, interviews, and field notes. The findings revealed that cooperative learning, particularly side-by-side pair work and Learning Together group models, improved students’ reading comprehension, with student performance rising from 60% (fair) to 73% (good) across two meetings. However, challenges such as students’ unfamiliarity with group work, gender pairing issues, and over-reliance on dictionaries were identified. The study concludes that cooperative learning is effective in enhancing reading comprehension and recommends that teachers systematically introduce the strategy, minimize immediate intervention, and foster positive interdependence among students. Rendahnya capaian pemahaman bacaan siswa sekolah menengah pertama di Indonesia masih menjadi isu krusial dalam pembelajaran bahasa Inggris. Peta masalah utamanya adalah apakah pembelajaran kooperatif dapat mengatasi masalah ini dengan mengubah pendekatan dari guru-sentris menjadi siswa-sentris. Penelitian ini bertujuan untuk mendeskripsikan proses pengajaran membaca dengan pendekatan kooperatif dan meningkatkan pemahaman bacaan siswa. Untuk mencapai tujuan tersebut, peneliti menggunakan desain Penelitian Tindakan Kelas (PTK) berdasarkan model Kemmis dan McTaggart, dengan menerapkan satu siklus perencanaan, tindakan, observasi, dan refleksi di SMP Islam Jember tahun ajaran 2006/2007. Data dikumpulkan melalui lembar observasi, hasil kuis, wawancara, dan catatan lapangan. Temuan penelitian menunjukkan bahwa pembelajaran kooperatif, khususnya model pasangan berdampingan dan kelompok Learning Together, meningkatkan pemahaman membaca siswa, dengan peningkatan kinerja siswa dari 60% (cukup) menjadi 73% (baik) dalam dua pertemuan. Meskipun demikian, tantangan seperti ketidakterbiasaan siswa dengan kerja kelompok, masalah pasangan beda jenis kelamin, dan ketergantungan berlebih pada kamus juga teridentifikasi. Penelitian ini menyimpulkan bahwa pembelajaran kooperatif efektif untuk meningkatkan pemahaman membaca. Rekomendasinya adalah guru perlu memperkenalkan strategi secara sistematis, mengurangi intervensi langsung, dan menumbuhkan interdependensi positif.